Finance and Development, June 1975. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1975)
This paper reviews the procurement process under World Bank projects. The paper highlights that the World Bank's interest in procurement under its loans stems directly from the 'project' requirement of its Articles, which stipulates that it should lend for specific projects, except in special circumstances, and that it should ensure that the proceeds of the loan are used only for its specified purpose, with due attention to economy and efficiency. In 1951, the World Bank began introducing international competitive bidding as the normal procedure for procurement of the goods and works needed for its projects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet